Serum Calprotectin and Iron Metabolism Biomarker Levels in Behçet's Disease - Ahmet Karadağ; Halef Okan Doğan (Galenos Yayinevi, 2021)
Objective:This study aimed to investigate the serum levels of calprotectin, hepcidin, iron, and ferritin in Behçet's disease (BD).Materials and Methods:This study included 40 patients with BD who met the diagnostic criteria of the BD International Study Group (1990) and 40 healthy control participants. Serum high-sensitive C-reactive protein (hsCRP), hepcidin, calprotectin, ferritin, iron, and unsaturated iron-binding capacity (UIBC) levels were determined in all study participants.Results:Statistically significant difference was found between the groups in respect of calprotectin (p<0.05), UIBC (p<0.05), hsCRP (p<0.05), and hemoglobin (p<0.05) levels. No statistically significant differences were determined between the patients and the controls in terms of hepcidin, iron, and ferritin levels. Cut-off value of 212.3 pg/mL for calprotectin was determined to identify patients with BD having a sensitivity and specificity of 100% and 90%, respectively.Conclusion:Serum calprotectin may be a useful biomarker in the evaluation of inflammatory status and BD diagnosis. Total iron-binding capacity and hemoglobin may be more useful in evaluating iron deficiency anemia in patients with BD.